Understanding the dynamics of evacuation delays: A study of the 2021 mount Semeru eruption through PLS-SEM analysis - I Dewa Made Frendika Septanaya; Adjie Pamungkas; Anoraga Jatayu; Rivan Aji Wahyu Dyan Syafitri; Amien Widodo; Mayra Andrakayana (Progress in Disaster Science)
This study explores the key factors contributing to evacuation delays during the 2021 eruption of Mount Semeru in Indonesia. Using Partial Least Squares Structural Equation Modelling (PLS-SEM), data were collected from 100 affected residents to examine behavioural responses and decision-making dynamics during the crisis. The analysis tested eight hypotheses and found that five were statistically significant, indicating that lack of information, emotional attachment to property, absence of evacuation plans, limited infrastructure, and family-related concerns were positively associated with delayed evacuation decisions. Notably, 71 % of respondents relied on neighbours as their primary information source, and 80 % reported experiencing panic during the evacuation process. These findings highlight critical gaps in community preparedness and emergency communication systems. The study concludes that strengthening early warning dissemination, enhancing infrastructure, conducting regular evacuation drills, and addressing socio-emotional factors are essential to improving evacuation effectiveness. This research contributes to a deeper understanding of evacuation behaviour during volcanic disasters and offers practical recommendations to enhance community resilience and emergency management practices.